Assessment of tools for urban energy planning. (1st June 2019) - Ferrari, Simone; Zagarella, Federica; Caputo, Paola; Bonomolo, Marina
Abstract: In recent years, studies and policies have encouraged the diffusion of distributed energy supply technologies and large integration of renewable sources. This increases the need for new professionals in energy planning. Several computational tools for energy planning have been developed as described in the technical literature. However, energy planners of urban/district areas engaged in the transition towards smart systems related to buildings energy services require well-documented tools to evaluate the combination of available energy sources by proper conversion technologies. With this, after a scientific review, we selected 17 tools targeted on an urban/districts scale that can evaluate several energy services, sources and/or technologies, and provided with detailed and easily accessible documentation. These tools were classified based on their defined features: analysis type, operation spatial scale, outputs time scale, energy service, and licence. Among them, 6 user-friendly tools were identified (energyPRO, HOMER, iHOGA, EnergyPLAN, SIREN, WebOpt) that can provide hourly energy calculations and can be considered as viable for widespread use. Specifically, the general information, functionalities, structure, graphic user interface, required input data, and outputs were described. Therefore, the energy planners are guided towards choosing the most suitable tool based on their skills, aims, and data availability for a specific application. Highlights: A review of tools for planning energy systems of urban building sector is presented. 17 tools have been selected by precise criteria and classified. 6 detailed user-friendly tools have been highlighted as viable of widespread use. Energy planners are supported in the tool choice, based on skills, aims and held data.